A teoria do “desenvolvimento fragmentador” - Scholz, Fred; Sutermeister, Paul (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2010)
In the past, the school of thought in Development Studies was dominated by the concept that lessdeveloped Third World countries could catch up with technical, financial and personal support from countries of the Northern hemisphere. The goal was to achieve a development level similar to the standards provided by western industrialized countries.